2021
DOI: 10.1186/s12870-020-02806-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis reveals that the Heterosis of two maize hybrids is related to enhancement of stress response and photosynthesis respectively

Abstract: Background Heterosis refers to superior traits exhibiting in a hybrid when compared with both parents. Generally, the hybridization between parents can change the expression pattern of some proteins such as non-additive proteins (NAPs) which might lead to heterosis. ‘Zhongdan808’ (ZD808) and ‘Zhongdan909’ (ZD909) are excellent maize hybrids in China, however, the heterosis mechanism of them are not clear. Proteomics has been wildly used in many filed, and comparative proteomic analysis of hybri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…For instance, a study on heterosis manifestation in cotton ( Gossypium hirsutum ) hybrid “Huaza Mian H318” uncovered that enhanced photosynthesis and carbohydrate metabolism facilitated heterosis in H318 during the seeding stage [ 72 ]. Similar results were also found in studies on heterosis in maize and Brassica napus [ 73 , 74 ]. Interestingly, in this study, results comparable to the outcomes discussed above were found through KEGG analyses, that is, significant DEGs were related to photosynthetic-efficiency- and glyco-metabolism-related pathways, such as peroxisomes, carbon metabolism, glycolysis/gluconeogenesis, and citrate cycle (TCA cycle).…”
Section: Discussionsupporting
confidence: 90%
“…For instance, a study on heterosis manifestation in cotton ( Gossypium hirsutum ) hybrid “Huaza Mian H318” uncovered that enhanced photosynthesis and carbohydrate metabolism facilitated heterosis in H318 during the seeding stage [ 72 ]. Similar results were also found in studies on heterosis in maize and Brassica napus [ 73 , 74 ]. Interestingly, in this study, results comparable to the outcomes discussed above were found through KEGG analyses, that is, significant DEGs were related to photosynthetic-efficiency- and glyco-metabolism-related pathways, such as peroxisomes, carbon metabolism, glycolysis/gluconeogenesis, and citrate cycle (TCA cycle).…”
Section: Discussionsupporting
confidence: 90%
“…Carbon-fixation-related proteins had a mixed pattern of expression differences in the hybrid and overall were neither positively nor negatively correlated with plant height heterosis. Others report that hybrids are associated with either elevated levels of photosynthetic proteins (hybrid ZD909) or stress proteins (hybrid ZD808), but not both ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…They detected 85 proteins that non-additively accumulate in at least one hybrid, and the result indicated that the increase of hybrid protein synthesis rate might be related to the early performance of hybrid vigor in seminal roots. Wang et al (2021) identified over 2000 proteomes from maize hybrids and their parents’ seedling leaves via label-free quantification. Moreover, they verified four stress-related proteins and eight photosynthetic-related proteins via parallel reaction monitoring.…”
Section: Transcriptomics and Proteomics Reveal Plant Heterosismentioning
confidence: 99%
“…Hybrids are superior to parents in terms of yield, growth rate, viability, and disease resistance (Hochholdinger and Hoecker, 2007). In agricultural production, heterosis is widely utilized in animals, such as silkworms, and plants, such as rice, maize, vegetables, and some perennials (Vaillancourt et al, 1995;Arcade et al, 1996;Kopp et al, 2002;Marcelo et al, 2007;Costa et al, 2014;Chen et al, 2020;Wang et al, 2021;Yu et al, 2021;Zhang et al, 2021). The use of heterosis has gradually improved the yield, quality, and disease resistance of animals and plants, thereby enhancing the social and economic benefits of agricultural production.…”
Section: Introductionmentioning
confidence: 99%